2021
DOI: 10.1002/asia.202100534
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure‐Photophysics Evaluation of 2‐N‐Amino‐quinazolines: Small Molecule Fluorophores for Solution and Solid State

Abstract: 2‐N‐aminoquinazolines were prepared by consecutive SNAr functionalization. X‐ray structures display the nitrogen lone pair of the 2‐N‐morpholino group in conjugation with the electron deficient quinazoline core and thus representing electronic push‐pull systems. 2‐N‐aminoquinazolines show a positive solvatochromism and are fluorescent in solution and in solid state with quantum yields up to 0.73. Increase in electron donor strength of the 2‐amino substituent causes a red‐shift of the intramolecular charge tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 100 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Over the last two decades, there has been a remarkable increase in the number of fluorescent diaza-heterocycles [ 1 , 2 , 3 , 4 ]. Among them quinoxaline and quinazoline derivatives are considered as pH sensors [ 5 , 6 , 7 ], luminescent detectors [ 8 , 9 , 10 ], imaging agents [ 11 ], components for organic light-emitting diodes (OLED) materials [ 12 , 13 ], solar cells and organic photovoltaic [ 14 , 15 ], and so on. The fundamental work has been done for the establishment of detailed structure–property relationships (SPRs) providing beneficial information for fine-tuning of the key properties and the rational design and synthesis of fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, there has been a remarkable increase in the number of fluorescent diaza-heterocycles [ 1 , 2 , 3 , 4 ]. Among them quinoxaline and quinazoline derivatives are considered as pH sensors [ 5 , 6 , 7 ], luminescent detectors [ 8 , 9 , 10 ], imaging agents [ 11 ], components for organic light-emitting diodes (OLED) materials [ 12 , 13 ], solar cells and organic photovoltaic [ 14 , 15 ], and so on. The fundamental work has been done for the establishment of detailed structure–property relationships (SPRs) providing beneficial information for fine-tuning of the key properties and the rational design and synthesis of fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…To support this evidence, we performed a fluorescence study for the resulting solution, and it was compared with that solution in the absence of an oxidant. It is documented that 2-aminoquinazolines present fluorescence properties with a normal emission at 400–430 nm and a secondary anomalous at 575–600 nm. It is well known that the fluorometry is a high-sensitivity technique, which facilitated the detection of low-concentration compounds. From the fluorescence experiment, in general, all 2-arylquinazolin-4-hydrazines showed a maximum normal emission wavelength at 400 nm (Figures B–D and S8 and S9).…”
Section: Resultsmentioning
confidence: 99%
“…Each of the fragments is of great interest owing to their electron withdrawing properties and use in the design of donor-acceptor small molecules displaying characteristics preferable for optical materials. The quinazoline component has been explored in the context of fundamental research [3][4][5], with some quinazoline derivatives revealed to have potential application in optoelectronics [6][7][8][9], detection of analytes [10,11], bioimaging [12], etc. [1,2,4]Triazole derivatives, in turn, are considered as blue phosphorescent, TADF emitters or host materials for OLED devices [13][14][15].…”
Section: Introductionmentioning
confidence: 99%